1991
DOI: 10.1152/ajpheart.1991.260.1.h13
|View full text |Cite
|
Sign up to set email alerts
|

Importance of endothelium-derived nitric oxide in porcine coronary resistance arteries

Abstract: Endothelial cells regulate vascular tone through the release of nitric oxide and other relaxing factors. The role of these substances was studied in isolated intramyocardial porcine coronary resistance arteries suspended in myographs for isometric tension recording. The inhibitor of nitric oxide formation NG-monomethyl-L-arginine (L-NMMA; 10(-7)-10(-4)M), but not D-NMMA, caused endothelium-dependent contractions that could be reversed by L-arginine but not by D-arginine. In preparations with endothelium, L-NMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
53
1
2

Year Published

1991
1991
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 0 publications
10
53
1
2
Order By: Relevance
“…Such an heterogeneous release of EDRF has already been reported in isolated dog coronary arteries (Hoeffner et al, 1989). In isolated small coronary arteries of the pig (Tschudi et al, 1991), and in pressurized mesenteric resistance arteries of the rat (Dohi et al, 1990), administration of L-NMMA induced vasoconstriction, suggesting that these vessels do release nitric oxide from L-arginine under basal conditions, at least in vitro. However, in these experiments, only the larger (>100pum diameter) resistance arteries were studied, and those contribute to less than 50% of total resistance in various vascular beds, including the coronary circulation (Chillian et al, 1986).…”
Section: Discussionsupporting
confidence: 57%
“…Such an heterogeneous release of EDRF has already been reported in isolated dog coronary arteries (Hoeffner et al, 1989). In isolated small coronary arteries of the pig (Tschudi et al, 1991), and in pressurized mesenteric resistance arteries of the rat (Dohi et al, 1990), administration of L-NMMA induced vasoconstriction, suggesting that these vessels do release nitric oxide from L-arginine under basal conditions, at least in vitro. However, in these experiments, only the larger (>100pum diameter) resistance arteries were studied, and those contribute to less than 50% of total resistance in various vascular beds, including the coronary circulation (Chillian et al, 1986).…”
Section: Discussionsupporting
confidence: 57%
“…The minimal influence of LNA on the CBFv response is consistent with that reported in porcine coronary resistance arteries. 21 This CBFv response to bradykinin, which is resistant to inhibitors of NO synthase, may be mediated by endothelium-derived hyperpolarizing factor (EDHF), because it has been shown that the relaxing response of coronary vessels to bradykinin is also mediated by EDHF, which probably acts through calcium-activated potassium channels. 22,23 However, the in vivo role of EDHF remains unknown because EDHF has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05; **P < 0.01. (Richard et al, 1990;Cocks & Angus, 1991;Tschudi et al, 1991). Consequently, mediators other than NO, are required to explain the coronary vasodilator effect of BK.…”
Section: Discussionmentioning
confidence: 99%